Stabilization of large drainage basins over geological time scales: Cenozoic West Africa, hot spot swell growth, and the Niger River. (26th March 2016) - Chardon, Dominique; Grimaud, Jean‐Louis; Rouby, Delphine; Beauvais, Anicet; Christophoul, Frédéric
Abstract: Reconstructing the evolving geometry of large river catchments over geological time scales is crucial to constraining yields to sedimentary basins. In the case of Africa, it should further help deciphering the response of large cratonic sediment routing systems to Cenozoic growth of the basin‐and‐swell topography of the continent. Mapping of dated and regionally correlated lateritic paleolandscape remnants complemented by onshore sedimentological archives allows the reconstruction of two physiographic configurations of West Africa in the Paleogene. Those reconstructions show that the geometry of the drainage is stabilized by the late early Oligocene (29 Ma) and probably by the end of the Eocene (34 Ma), allowing to effectively link the inland morphoclimatic record to offshore sedimentation since that time, particularly in the case of the Niger catchment—delta system. Mid‐Eocene paleogeography reveals the antiquity of the Senegambia catchment back to at least 45 Ma and suggests that a marginal upwarp forming a continental divide preexisted early Oligocene connection of the Niger and Volta catchments to the Equatorial Atlantic Ocean. Such a drainage rearrangement was primarily enhanced by the topographic growth of the Hoggar hot spot swell and caused a stratigraphic turnover along the Equatorial margin of West Africa. Key Points: Stability of West African drainage documented since early Oligocene Drainage rearrangement triggered by late Eocene Hoggar hot spot swell growth Implications for source‐to‐sink studies and landform/river network evolution processes